Analysis of Risk Factors for Kidney Retransplant Outcomes Associated with Common Induction Regimens: A Study of over Twelve-Thousand Cases in the United States - Alfonso H. Santos; Michael J. Casey; Karl L. Womer (Journal of Transplantation)
We studied registry data of 12,944 adult kidney retransplant recipients categorized by induction regimen received into antithymocyte globulin (ATG) (N = 9120), alemtuzumab (N = 1687), and basiliximab (N = 2137) cohorts. We analyzed risk factors for 1-year acute rejection (AR) and 5-year death-censored graft loss (DCGL) and patient death. Compared with the reference, basiliximab: (1) one-year AR risk was lower with ATG in retransplant recipients of expanded criteria deceased-donor kidneys (HR = 0.56, 95% CI = 0.35–0.91 and HR = 0.54, 95% CI = 0.27–1.08, resp.), while AR risk was lower with alemtuzumab in retransplant recipients with >3 HLA mismatches before transplant (HR = 0.63, 95% CI = 0.44–0.93 and HR = 0.81, 95% CI = 0.63–1.06, resp.); (2) five-year DCGL risk was lower with alemtuzumab, not ATG, in retransplant recipients of African American race (HR = 0.54, 95% CI = 0.34–0.86 and HR = 0.73, 95% CI = 0.51–1.04, resp.) or with pretransplant glomerulonephritis (HR = 0.65, 95% CI = 0.43–0.98 and HR = 0.82, 95% CI = 0.60–1.12, resp.). Therefore, specific risk factor-induction regimen combinations may predict outcomes and this information may help in individualizing induction in retransplant recipients.